2019
DOI: 10.1021/acs.jmedchem.9b01032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CNS-Penetrant Aryl Sulfonamides as Isoform-Selective NaV1.6 Inhibitors with Efficacy in Mouse Models of Epilepsy

Abstract: Nonselective antagonists of voltage-gated sodium (Na V ) channels have been long used for the treatment of epilepsies. The efficacy of these drugs is thought to be due to the block of sodium channels on excitatory neurons, primarily Na V 1.6 and Na V 1.2. However, these currently marketed drugs require high drug exposure and suffer from narrow therapeutic indices. Selective inhibition of Na V 1.6, while sparing Na V 1.1, is anticipated to provide a more effective and better tolerated treatment for epilepsies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 64 publications
0
41
0
Order By: Relevance
“…In the case of the inhibitor (12), its disruption of the PPI between FGF14 and Nav1.6 could be conferred via direct binding to the FGF14 interaction site on the C-terminal tail of Nav1.6 or via binding to FGF14 and causing the protein to undergo a conformational change that makes it inaccessible to its native interaction site on the C-terminal tail of Nav1.6. Similarly, for the potentiator of FGF14:Nav1.6 complex assembly (19), its modulatory effects on the PPI could be conferred by both binding to the C-terminal tail of Nav1.6 that makes the FGF14 interaction site increasingly accessible to the regulatory protein, or, conversely, by binding to FGF14 and causing it to undergo a conformational change that affords it with increased accessibility to its interaction site on the C-terminal tail of Nav1.6. In the native system, it is expected that the protein:ligand interactions of 12 and 19 with FGF14 and the C-terminal tail of Nav1.6 will concomitantly occur and collectively enable functionally relevant modulation of FGF14:Nav1.6 complex assembly.…”
Section: Fgf14mentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the inhibitor (12), its disruption of the PPI between FGF14 and Nav1.6 could be conferred via direct binding to the FGF14 interaction site on the C-terminal tail of Nav1.6 or via binding to FGF14 and causing the protein to undergo a conformational change that makes it inaccessible to its native interaction site on the C-terminal tail of Nav1.6. Similarly, for the potentiator of FGF14:Nav1.6 complex assembly (19), its modulatory effects on the PPI could be conferred by both binding to the C-terminal tail of Nav1.6 that makes the FGF14 interaction site increasingly accessible to the regulatory protein, or, conversely, by binding to FGF14 and causing it to undergo a conformational change that affords it with increased accessibility to its interaction site on the C-terminal tail of Nav1.6. In the native system, it is expected that the protein:ligand interactions of 12 and 19 with FGF14 and the C-terminal tail of Nav1.6 will concomitantly occur and collectively enable functionally relevant modulation of FGF14:Nav1.6 complex assembly.…”
Section: Fgf14mentioning
confidence: 99%
“…Heretofore, it had been shown that addition of a N-terminal benzoyl substituent (19) to tetrapeptide analogs produced an efficacious potentiator of FGF14:Nav1.6 complex assembly, whereas truncation to a tripeptide (12) yielded an inhibitor of the complex s assembly. Additionally, both 12 and 19 demonstrated promising protein:ligand binding interactions.…”
Section: Electrophysiological Evaluation Of Compounds 12 and 19mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, chloropyrazine derivatives, specifically anilides of 6-chloropyrazine-2-carboxylic acid, were proven previously to possess in vitro antimycobacterial activity [18,19]. Generally, sulfonamides exert a wide range of biological activities, including anti-tumoral [5], anti-inflammatory [6], anti-convulsant [7], and anti-infective [8], among others. Nevertheless, several compounds containing a pyrazine core directly connected to a sulfonamide moiety-like in our case-are already documented in the literature with a wide range of pharmacological applications [9].…”
Section: Chemistrymentioning
confidence: 99%
“…Generally, sulfonamides exert a wide range of biological activities, including anti-tumoral [5], anti-inflammatory [6], anti-convulsant [7], and anti-infective [8], among others. Nevertheless, Generally, sulfonamides exert a wide range of biological activities, including anti-tumoral [5], anti-inflammatory [6], anti-convulsant [7], and anti-infective [8], among others. Nevertheless, several compounds containing a pyrazine core directly connected to a sulfonamide moiety-like in our case-are already documented in the literature with a wide range of pharmacological applications [9].…”
Section: Introductionmentioning
confidence: 99%